Results of a course on news analysis in social networks and epistemological beliefs - Meza Cano, José Manuel; González Santiago, Edith; Cañizales Espinosa, Mariana; Morales Ruiz, Mario Ernesto (Emerging Trends in Education, 2024)
The Internet is currently the most relevant source of information; however, it is necessary to know how to distinguish news whose content may be malicious, misleading, or false. Much has been emphasized on the skills to analyze fake news from its structure, hand in hand with media literacy, but little work has been done on the psychological variables of the participants that can prevent them from accepting fake news without critical analysis. In this sense, epistemological beliefs are a variable to be taken into account. In this paper, we analyzed the results of a three-week course of news analysis in social networks on epistemological beliefs, including topics on cognitive biases and media literacy. Fifty-eight higher education students and 22 graduate students participated. Subsequently, we verified the change in epistemological beliefs by applying the Internet-Specific Epistemological Beliefs Questionnaire in two measurements, pretest, and posttest, in two editions of the course. As a result, we detected statistically significant changes in two components that favored the participant's perspective as a knowledge builder and the Internet as a questionable source. We concluded that it is necessary to continue with this model of instruction to empower news readers to make better decisions regarding the information they receive.
Keywords: fake news; disinformation; epistemology; social networks; higher education